Prevalence of chronic obstructive pulmonary disease among adults in Kashmir (North India): a population based study - Hanga, Asif Jeelani; Mir, Irfan Nazir; Ahmad, Mir Mujtaba; Raja, Waseem; Aleem, Seema (International Journal Of Community Medicine And Public Health, 2018)
Background: Chronic obstructive pulmonary disease (COPD), represents an important public health challenge that is both preventable and treatable. This study provides population based spirometry data on the burden of COPD in adult population of Kashmir Valley. Objectives of the study were to estimate the prevalence of chronic obstructive pulmonary disease and its associated risk factors in age group 40 years and above among Kashmiri population. Methods: This study was conducted from April 2012 to December 2014. Multi stage gender stratified cluster sampling was employed to select 30 clusters from two blocks of Kashmir. A total of 504 males and 521 females performed acceptable spirometry after providing information on personal characteristics and relevant risk factors. Participants: Adults aged 40 years and above of Kashmiri ethnicity with no contraindication for spirometry. Variables: Proportion of subjects with FEV1/FVC less than 0.70, percent predicted FEV1 and FVC. Statistical methods: Descriptive statistics using frequencies, chi square test. Results: Overall prevalence of COPD at stage I or higher was 15.90%, and was higher in males (19.05) than in females (12.08). The prevalence of Grade 1, 2, 3 and 4 COPD was 8.8%, 5.2%, 1.4% and 0.6% respectively. Chronic obstructive pulmonary disease (COPD) prevalence was associated with increased age and tobacco smoking. COPD prevalence was 2.7%, 22%, 28.2% in non-smokers, ex-smokers and current smokers respectively. 59.5% subjects had a positive history of tobacco exposure. Conclusions: This study concludes that there is a high prevalence of COPD in Kashmir, high prevalence of COPD is attributed to high incidence of tobacco smoking in the study population.